A Minimum Operator Based Discrete-Time Super-Twisting-Like Algorithm - Prasun P.; Pandey S.; Kamal S.; Ghosh S.; Xiong X. (My University, 2025)
In this brief, a minimum operator (MO) based approach is proposed for discrete-time super-twisting-like algorithm which has different roots unlike its contemporaries, most of which are based on Euler-discretization (ED). The algorithm is proposed for both unperturbed and perturbed cases. The application of this algorithm is further explored for the super-twisting observer (STO) that yields the finite-time estimation of the system states. An illustrative example of a pendulum system with known as well as unknown input is considered for the state observation problem. Simulation results show the effectiveness of the proposed algorithm. © 2023 IEEE.